Breaking the Scaling Relationship in Water Oxidation Enabled by the Electron Buffering Effect of the Fullerene Network - Chen, Xiang; Ma, Hao; Wang, Xing; Jin, Hongqiang; Wu, Yao; Wang, Sibo; Xiao, Yukun; Jiang, Rui; Da, Yumin; Fan, Lei; Sun, Yuanmiao; Xi, Shibo; et al. (Journal of the American Chemical Society, 2025)
The scaling relationship among reaction intermediates with strongly correlated adsorption energy in the oxygen evolution reaction (OER) severely restricts the energy-conversion efficiency of water electrolysis. For the conventional adsorbate evolution mechanism, breaking the scaling relationship remains challenging, as it is difficult to modulate the adsorption of multiple intermediates on a specific active site simultaneously. Herein, we utilize the electron buffering effect of a two-dimensional fullerene network (C60NET) to dynamically tune the electronic structure of the iridium (Ir) active site with the change of adsorbed intermediates, which can tailor the adsorption strength of intermediates from multistep reactions and break the adsorption-energy scaling relationships among *OOH, *O, and *OH. The C60NET-buffered Ir nanocluster catalyst exhibits excellent OER activity with a low overpotential of 237 mV and stability over 600 h at 10 mA cm–2, outperforming graphene-supported Ir nanoclusters and commercial IrO x , attributed to the breaking of the linear scaling relationship enabled by the unique ability to reversibly accept and donate electrons of C60NET.